Implementasi Kepemimpinan Pembelajaran Kepala Madrasah Di Madrasah Aliyah Pembangunan - Rusli Rusli (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2020)
This paper discusses the learning leadership of the Madrasah Principal in Madrasah Aliyah (MA) Pembangunan. The principal of the madrasah as a leader is responsible for the course of the learning process in schools. A successful learning process will increase learning achievement and student satisfaction and motivation to learn higher. The principal as a learning leader is leadership that emphasizes components that are closely related to learning, including curriculum, teaching and learning processes, assessment, assessment, teacher development, excellent service in learning, and building learning communities in schools. The main objective of learning leadership is to provide excellent service to all students so that they are able to develop their potential, talents, interests and needs. Learning leadership is also aimed at facilitating learning so that student learning achievement increases, learning satisfaction is higher, learning motivation is higher, curiosity is realized, creativity is fulfilled, innovation is realized, an entrepreneurial spirit is formed, and awareness for lifelong learning because of science and technology and art developing rapidly growing well. Learning leadership if applied in schools will be able to build learning communities for its citizens and even be able to make the school a learning school